Ex vivo dual perfusion of an isolated human placenta cotyledon: Towards protocol standardization and improved inter-centre comparability. (August 2022) - Schneider, Henning; Albrecht, Christiane; Ahmed, Mahmoud S.; Broekhuizen, Michelle; Aengenheister, Leonie; Buerki-Thurnherr, Tina; Danser, A.H. Jan; Gil, Sophie; Hansson, Stefan R.; Greupink, Rick; Lewis, Rohan M.; Markert, Udo R.; et al.
Abstract: Since the full development of the ex vivo dual perfusion model of the human placenta cotyledon, the technique has provided essential insight into how nutrients, lipids, gases, immunoglobulins, endocrine agents, pharmaceuticals, chemicals, nanoparticles, micro-organisms and parasites might traverse the maternofetal barrier. Additionally, the model has been instrumental in gaining a better understanding of the regulation of vascular tone, endocrinology and metabolism within this organ. The human placenta is unique amongst species in its anatomy and transfer modalities. This orthologous diversity therefore requires an appropriate consideration of placental transfer rates of compounds, particles and micro-organisms specific to humans. Different research centres have adapted this model with a wide variation in perfusion parameters, including in the establishment of perfusion, perfusate composition, gassing regime, cannulation method, flow rates, perfused tissue mass, and also in the application of quality control measures. The requirement to harmonise and standardise perfusion practice between centres is largely driven by the need to obtain consistency in our understanding of placental function, but also in the qualification of the model for acceptance by regulatory agencies in drug and toxicology testing. A pilot study is proposed, aiming to describe how existing inter-centre variation in perfusion methodology affects placental metabolism, protein synthesis, oxygen consumption, the materno-fetal transfer of key molecular markers, and placental structure. Highlights: Ex vivo dual perfusion of the human placenta explores placental transfer and function. Methodology variation might impact on the basic physiology and anatomy of the tissue. Toxicology regulators are driving alternatives to animal use in development testing. A multi-centre pilot will standardise ex vivo human placenta dual perfusion.